2023
DOI: 10.2147/jir.s399786
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Salivary Cytokines, Chemokines and Growth Factors and Salivary Gland Function in Children with Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is a systemic inflammatory disease that leads to multiple organ complications not only in the kidneys and the cardiovascular system, but also in the oral cavity. CKD children experience reduced saliva secretion (hyposalivation), which leads to increased incidence of dental caries and significant impairment of patients' quality of life. However, the causes of salivary gland dysfunction in children with CKD are unknown. The present study is the first to evaluate the inflammatory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…This is consistent with the results of other authors. 8,15,22 Comparing cytokine levels such as IL-5, IL-10, IL-17A, and IL-12p70, which play important roles in regulating the immune response, can help to understand the differences between the inflammatory and tissue regeneration processes. 22 Additionally, Eotaxin, Rantes, VEGF, and IP-10 are chemokines that play a significant role in the chemotaxis and recruitment of different types of cells to sites of infection or inflammation, which can influence the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results of other authors. 8,15,22 Comparing cytokine levels such as IL-5, IL-10, IL-17A, and IL-12p70, which play important roles in regulating the immune response, can help to understand the differences between the inflammatory and tissue regeneration processes. 22 Additionally, Eotaxin, Rantes, VEGF, and IP-10 are chemokines that play a significant role in the chemotaxis and recruitment of different types of cells to sites of infection or inflammation, which can influence the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Biomolecules can be translocated from the blood to saliva via intracellular (diffusion, filtration, active transport) or extracellular (ultrafiltration, transport across damaged membranes) transport mechanisms. Biomolecules are also produced by the salivary glands [ 36 ]. Interestingly, the salivary glands are highly sensitive to oxidative damage [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several causes of xerostomia in CKD have been studied in literature, yet, the definitive cause is still unknown. [36] Postorino et al [37] reported the presence of salivary gland fibrosis and atrophy in ESRF patients which manifested clinically in xerostomia.…”
Section: Developmental Defects Of Enamelmentioning
confidence: 99%
“…Patients on HD are also advised to limit fluid intake which may contribute to reduced salivary production. [38] Another study by Szulimowska et al [36] suggested the involvement of salivary cytokines, chemokines, and growth factors with salivary gland dysfunction as these molecules are produced as a result of persistent inflammation in salivary glands affecting the function of acinar cells.…”
Section: Developmental Defects Of Enamelmentioning
confidence: 99%